2013
DOI: 10.1039/c3tb20323a
|View full text |Cite
|
Sign up to set email alerts
|

Development of a versatile biotinylated material based on SU-8

Abstract: The negative epoxy-based SU-8 photoresist has a wide variety of applications within the semiconductor industry, photonics and lab-on-a-chip devices, and it is emerging as an alternative to silicon-based devices for sensing purposes. In the present work, biotinylation of the SU-8 polymer surface promoted by light is reported. As a result, a novel, effective, and low-cost material, focusing on the immobilization of bioreceptors and consequent biosensing, is developed. This material allows the spatial discriminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…After that, the remains are eliminated with a PMMA industrial developer AR-600-55 (ALLRESIST GmbH, Strausberg, Germany) diluted 1:4 with propanol. When the BICELLs were manufactured chip by chip, the cleaning process was exhaustive [ 11 ]. However, fabrication at the wafer level drastically improves the yield because the cleaning process is reduced in a single rising step with dimethyl sulfoxide (DMSO).…”
Section: Methodsmentioning
confidence: 99%
“…After that, the remains are eliminated with a PMMA industrial developer AR-600-55 (ALLRESIST GmbH, Strausberg, Germany) diluted 1:4 with propanol. When the BICELLs were manufactured chip by chip, the cleaning process was exhaustive [ 11 ]. However, fabrication at the wafer level drastically improves the yield because the cleaning process is reduced in a single rising step with dimethyl sulfoxide (DMSO).…”
Section: Methodsmentioning
confidence: 99%
“…The SU8 surface of the BICELLs was treated with sulfuric acid (95% for 10 s) in order to have a hydrophilic sensing surface. As a result of this treatment, the SU8 epoxy groups are opened and suitable to immobilize covalently the protein [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…3−7 Moreover, SU-8 has optimal chemical stability and transparent to visible light after cross-linking, which can be used as optical waveguides, 8 probes for microscopy, 9 MEMS, 10−12 and molds for microchip. 13 Previous studies have shown that SU-8 could be nontoxic and biocompatible after polymerization, 14,15 indicating its potential to serve as the substrate of bioanalytical micro-and nanodevices, 16 such as biosensors, 17 bioarrays, 18 and drug delivery vehicles. 19 However, the hydrophobic nature of SU-8 has limited its biological applications in practice, which causes low specific adsorption of probes, 20 poor surface wettability, 21,22 and limited cell attachment.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Additionally, SU-8 is able to produce microstructure with high aspect ratio with a wide range of structure thickness. Moreover, SU-8 has optimal chemical stability and transparent to visible light after cross-linking, which can be used as optical waveguides, probes for microscopy, MEMS, and molds for microchip . Previous studies have shown that SU-8 could be nontoxic and biocompatible after polymerization, , indicating its potential to serve as the substrate of bioanalytical micro- and nanodevices, such as biosensors, bioarrays, and drug delivery vehicles …”
Section: Introductionmentioning
confidence: 99%